Synovial and pulmonary dysfunctions are induced by crosstalk of Smad and Erk pathways in an arthritis model - Lei, Wan; Jian, Liu; Chuanbing, Huang; Xi, Chen; Lei, Liu; Tianyang, Liu; Yao, Ge; Haixia, Fan; Lei, Zhao; Zhneg, Li (Cellular and Molecular Biology, 2020)
In the current experiment, the effects of transforming growth factor (TGF)-Î²1/Smad and ERK pathway crosstalk on synovial and pulmonary systems during rheumatoid arthritis have been investigated. For this purpose, rats were divided into normal control (NC) and model control (MC) groups. In the MC group, 0.1 ml Freund's complete adjuvant was injected intradermally into the right hind paw, and the resulting inflammation represented a rheumatoid arthritis model. Joint swelling and changes in lung functions were observed in arthritic rats. Synovial and lung were observed by light and electron microscopies. Enzyme-linked immunosorbent assays were used to detect TGF-Î²1, interleukin (IL)-1Î², IL-4, IL-10, interferon-Î³ (IFN-Î³), connective tissue growth factor (CTGF), and fibroblast growth factor (FGF). PCR, immunohistochemistry, and immunoblotting were used to detect changes in Smad and ERK pathways of synovial and lung tissues. Compared with the NC group, toe swelling was elevated in the MC group. Pulmonary functions FEV1, FEF50, FEF75, MMF, and PEF were decreased (P< 0.01). Serum cytokines IL-1Î², IL-4, TGF-Î²1, and CTGF were increased, while IFN-Î³, IL-10, Th1/Th2 cell ratio, and FGF were decreased (P< 0.01 or P< 0.05). Expression of TGF-Î²1 and Smad2/3/4 mRNAs and TGF-Î²1, TÎ²RI, TÎ²RII, Smad2/3, p-Smad2/3, and Smad4 proteins in the synovial membrane and lung tissue were increased, and expression of Smad7 mRNA and protein was decreased (P<0.01) or P<0.05). Expression of ERK2 mRNA and p-ERK1/2 protein was increased in the synovial membrane and lung tissue, and expression of ERK1/2 mRNAs and ERK1/2 and p-ERK1/2 proteins was increased in lung tissue (P< 0.01 or P< 0.05). Correlation analysis showed that FEV1 was negatively correlated with TGF-Î²1 mRNA and protein in arthritic rats, FEF25 was negatively correlated with Smad4 protein, and FEF50 was negatively correlated with the TÎ²RII protein, and FEF75, TGF-Î²1 and Smad3 mRNAs. There was a negative correlation between Smad2/3 protein and a negative correlation between PEF and TGF-Î²1 protein (P< 0.05). FEF50 and MMF were positively correlated with Smad7 mRNA (P< 0.05). FEV1 was negatively correlated with ERK2 mRNA, and FEF25 was negatively correlated with p-ERK1/2 protein. FEF75 and MMF were negatively correlated with ERK1/2 and p-ERK1/2, respectively (P< 0.05). ERK1 mRNA was positively correlated with Smad3 mRNA and TÎ²RII protein, ERK2 mRNA was positively correlated with p-Smad2/3, and ERK1/2 protein was positively correlated with Smad2 mRNA, Smad4 protein, p-ERK1/2 protein, Smad4 mRNA, and p-Smad2/3 protein (P< 0.05). p-ERK1/2 protein was negatively correlated with Smad7 protein (P< 0.05). It is concluded that arthritic rats have synovial and systemic pulmonary damage. Smad and ERK pathway crosstalk leads to systemic lesions. Smad and ERK pathways are gradually activated by phosphorylation under the induction of the TGF-Î²1 promoter, and then participate in transcriptional activities, leading to the increase in synovial inflammation of arthritis, pulmonary lesions, and decreases in lung functions.